Online Education among Senior Secondary Students of Rural Area of Varanasi District: Prevalence and Challenges - Kumari, Pushpa; Mishra, Pooja (Indian Journal of Extension Education, 2024)
During the COVID-19 pandemic lockdown, online education emerged as an essential component of the education system to ensure learning continuity. In India, where online education wasn't traditionally integrated into the primary education system, assessing its influence on students is imperative. Understanding its effects is crucial for enhancing the quality of online education and gauging its impact on mental health. Our study aimed to evaluate the challenges encountered by senior secondary students in rural schools during the COVID-19 pandemic regarding online education. We examined the prevailing conditions and obstacles faced, while also analyzing the extent to which online education was adopted among them. The study was conducted in year 2022, among 431 senior secondary students. The students were selected through multistage sampling from two blocks of Varanasi i.e. Kashi Vidyapeeth and Chiraigoan. The results show that 39% of students were not aware of the online classes prior. The majority of students were using mobile devices to attend classes and for learning purposes. 52.2% expressed concerns about the students' mental health, and a large majority (95.4%) of students themselves worried about their academic careers.